E-Learning to Increase Employee Engagement during Covid-19 - Hudaya, Sabilul; Augusta, Helena; Furinto, Asnan; Tamara, Dewi (ExcelingTech, 2020)
Abstract E-learning has provided economic benefits for the bank and its staff. It can be interpreted that E-learning is a learning activity consisting of a series of application uses, namely the learning system via the web, virtual classes, or learning using computers. Through E-learning, staff can increase the knowledge and skills needed without disrupting work processes, regardless of time and space. At the same time, staff engagement is also an important factor for the bank to show whether the staff is motivated and productive. Therefore, this paper offers information regarding on e-learning and bank’s staff engagement before and during the COVID-19 situation, where the concept of social distancing must be applied to avoid the spread of the virus. Researchers used quantitative research methods in conducting research on staff from one of the top 10 banks in Indonesia based on total assets in 2019. In addition, the study explores mediating variables from Technology Acceptance Model (TAM) to explain the relationship between e-learning and staff engagement. However, because there are not many studies have been conducted regarding e-learning and staff engagement on this in the banking workplace, this paper furthermore can provide information on of remodeling learning methods with the adaptation of new ways of working. Keywords: E-learning, Employee Engagement, Bank, COVID-19 situation.